Green HRM Practices to Increase Green Creativity through Person Organization Fit in Employees of Glue Industry Companies in Surabaya - Laisoka, Duvan Samudra; Kusmaningtyas, Amiartuti; Riyadi, Slamet (PT Inovasi Pratama Internasional, 2025)
This study investigates the impact of Green Human Resource Management (Green HRM) practices on green creativity, mediated by person-organization fit among employees in the adhesive industry in Surabaya, Indonesia. Data were collected from 130 employees of PT X using a structured questionnaire. The results indicate that Green HRM practices positively influence person-organization fit, which in turn significantly enhances green creativity. Although Green HRM practices do not have a direct effect on green creativity, they foster an environment that supports innovative thinking by aligning employee values with organizational goals. These findings suggest that organizations can enhance green innovation by implementing comprehensive Green HRM practices that strengthen person-organization fit. This research contributes to the understanding of how Green HRM can be leveraged to promote sustainability and creativity within the manufacturing sector.